Virginia miscellany
Facsimile of a petition (1621) to the British ambassador to France to allow French and Walloon colonists to settle in Virginia; letter (circa 1658) of the Virginia Council to Richard Cromwell, another letter (1746) relating to lands in the Northern Neck purchased by Lord Thomas Fairfax, and fragment of a letter (1749) pertaining to Eleazer Robertson; three letters (1711, 1718) of the Virginia General Assembly documenting land sales by John and Frances Custis and Daniel McCarty; annotated chart (1748) showing results of a smallpox epidemic in Virginia; list (1757) of Virginia county surveyors; two letters (circa 1772-1775) of John Murray, Earl of Dunmore and governor of Virginia; photocopy, typescript, and facsimile of the Virginia Declaration of Rights (1776); and photocopy of a sketch (1781) of the Virginia commonwealth seal.
In part, photocopies and facsimiles.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Many items were previously cataloged separately.
Keywords: Custis, Frances Parke, -- 1687-1715.; Custis, John, -- 1678-1749.; Cromwell, Richard, -- 1626-1712 -- Correspondence; Dunmore, John Murray, -- Earl of, -- 1732-1809 -- Correspondence; Fairfax, Thomas Fairfax, -- Lord, -- 1692-1782.; McCarty, Daniel, -- 1678-1724.; Robertson, Eleazer; Virginia. -- Council; Virginia. -- General Assembly; Virginia; Land tenure -- Virginia; Smallpox -- Virginia; Surveyors -- Virginia; Belgium -- Colonies -- America; France -- Colonies -- America; Diplomatic and consular service, British -- France; Northern Neck (Va.); Virginia -- History -- Colonial period, ca. 1600-1775.; Virginia -- History -- Revolution, 1775-1783.; Virginia -- Politics and government -- To 1775.; Virginia -- Politics and government -- 1775-1793.; Virginia -- Seal